2002
DOI: 10.1111/j.1348-0421.2002.tb02663.x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Pharmacodynamic Characteristics of Amphotericin B against Trichosporon asahii, Using Time‐Kill Methodology

Abstract: We determined the MIC of amphotericin B against 45 Trichosporon asahii isolates from various clinical and environmental sources, and used in vitro time‐kill methods to characterize the relationship between amphotericin B concentrations and MIC for four representative T. asahii isolates. Amphotericin B had concentration‐dependent antifungal activity. MICs ranged from 0.5 to 16 μg/ml, and most T. asahii isolates (76%, 34/45) were inhibited at safely achievable amphotericin B serum concentrations (≤ 2 μg/ml). How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 23 publications
2
27
0
1
Order By: Relevance
“…While the susceptibility of unusual yeasts to antifungal agents varies, drug-resistant yeasts have been identified. Candida haemulonii, C. lusitaniae, Pichia farinosa, and Trichosporon asahii are resistant to amphotericin B (5,10,13,18). C. inconspicua, C. norvegensis, and some species of Rhodotorula are resistant to fluconazole (1,5).…”
Section: Discussionmentioning
confidence: 99%
“…While the susceptibility of unusual yeasts to antifungal agents varies, drug-resistant yeasts have been identified. Candida haemulonii, C. lusitaniae, Pichia farinosa, and Trichosporon asahii are resistant to amphotericin B (5,10,13,18). C. inconspicua, C. norvegensis, and some species of Rhodotorula are resistant to fluconazole (1,5).…”
Section: Discussionmentioning
confidence: 99%
“…1 Trichosporon asahii is now the species most often implicated in disseminated infections in neutropenic patients. 1,4 Treatment of systemic Trichosporon infection with conventional antifungal agents, such as amphotericin B and fluconazole, has generally been unrewarding, resulting in a crude mortality rate approximating 80%. 1,4 Recent studies have shown that voriconazole, a second-generation triazole, is highly active against T. asahii isolates in vitro.…”
mentioning
confidence: 99%
“…in immunocompromised patients, especially those with hematologic malignancies, are frequently associated with poor prognosis. [1][2][3][4] Since the taxonomic revision of the genus Trichosporon in 1992, it has been recognized that the formerly used designation Trichosporon beigelii includes several genetically distinct species. 1 Trichosporon asahii is now the species most often implicated in disseminated infections in neutropenic patients.…”
mentioning
confidence: 99%
“…Despite more than 40 years of clinical use, resistance to amphotericin B is very rare. Only C. lusitaniae, C. haemulonii, and Trichosporon asahii have reduced sensitivity to this drug (2,9,11,16). Although C. pseudohaemulonii and the two types of C. haemulonii are resistant to both amphotericin B and azole agents, they are very susceptible to 5-FC and micafungin.…”
mentioning
confidence: 99%